ANALYSIS OF DAILY SOCIAL MEDIA USAGE: A STUDY OF USER HABITS AND IMPACTS - Ehjaz Ahmad (Journal of Religion and Society, 2025)
Social media has profoundly influenced every aspect of human life over the past decade. The daily use of social media has become a common phenomenon, shaping individuals' personal lives, professional relationships, and social connections. These platforms are not only sources of entertainment but also serve as vital tools for information exchange, news dissemination, business growth, and supporting various social movements. This study aims to provide a detailed analysis of the daily usage of social media to understand how user habits are evolving and how this evolution impacts their daily routines and social lives. We will explore the popularity of different social media platforms, the various dimensions of their usage, and their psychological and social effects on users. The analysis will shed light on the increasing influence of social media on mental health, interpersonal relationships, and other critical aspects of human life. It will also explore the balance between the benefits and challenges posed by these platforms, offering insights into the implications of their growing integration into everyday life. This study seeks to answer key questions: How are social media habits changing? What are the primary drivers behind these changes? And, most importantly, what are the broader consequences of this growing dependency on social media for individual well-being and society as a whole? Keywords: Social Media, Daily Usage, User Habits, Psychological Impacts, Social Dynamics